QUALCHE RIFLESSIONE SULL’INTERAZIONE FRA UNIVERSITà€ E INDUSTRIA NEL SETTORE OTTICO-MECCANICO - Selvini, Attilio (GEOmedia, 2015)
In the twentieth century the Italian opticalmechanical industry reached, in the civil sector, primates worldwide certainly indisputable. However, the support provided by universities was modest, very modest, unlike what had happened for example in the same period in Germany.